Transient expression of Human papillomavirus type 16 L2 epitope fused to N- and C-terminus of coat protein of Potato virus X in plants - Čeřovská, Noemi; Hoffmeisterova, Hana; Moravec, Tomas; Plchová, Helena; Folwarczna, Jitka; Synkova, Helena; Ryslava, Helena; Ludvíková, Viera; Šmahel, Michal (Journal of biosciences, 2012)
Transient expression of foreign genes based on plant viral vectors is a suitable system for the production of relevant immunogens that can be used for the development of a new generation of vaccines against a variety of infectious diseases. In the present study the epitope derived from HPV-16 L2 minor capsid protein (amino acids 108-120) was expressed from Potato virus X (PVX)-based vector pGR106 as N- or C-terminal fusion with the PVX coat protein (PVX CP) in transgenic Nicotiana benthamiana plants. The fusion protein L2 108-120-PVX CP was successfully expressed in plants at a level of 170 mg/kg of fresh leaf tissue. The C-terminal fusion protein PVX CP- L2 108-120 was expressed using mutated vector sequence to avoid homologous recombination at a level of 8 mg/kg of fresh leaf tissue. Immunogenicity of L2 108-120-PVX CP virus-like particles was tested after immunization of mice by subcutaneous injection or tattoo administration. In animal sera the antibodies against the PVX CP and the L2 108-120 epitope were found after both methods of vaccine delivery.
Keywords: Epitopes; Animals; Microscopy, Electron, Transmission; Electrophoresis, Polyacrylamide Gel; Enzyme-Linked Immunosorbent Assay; virion; Female; Oligonucleotides; onkogenní proteiny virové; geneticky modifikované rostliny; oligonukleotidy; Blotting, Western; listy rostlin; Plants, Genetically Modified; ženské pohlaví; Recombinant Fusion Proteins; Virion; Capsid Proteins; Nicotiana; rekombinantní fúzní proteiny; lidé; Mice; Plant Leaves; myši; protilátky virové; imunizace; Immunization; western blotting; genetické vektory; ELISA; Cloning, Molecular; Oncogene Proteins, Viral; virové plášťové proteiny; klonování DNA; epitopy; zvířata; transmisní elektronová mikroskopie; Antibodies, Viral; Mice, Inbred C57BL; elektroforéza v polyakrylamidovém gelu; tabák; Genetic Vectors; myši inbrední C57BL; Humans